The impact of negative emotions on product purchase decisions: a study of watch design - Chao-Yang Yang; Ching-Yi Wang; Chang-Li Pao (BMC Psychology)
Abstract This study examines how emotional valence (positive and negative) impacts consumer purchasing decisions through wristwatch design, using visual geometric elements. By employing ERPs (Event-Related Potentials) neurophysiological measurements, the study objectively evaluates consumer emotional responses to design elements. Results show that negative emotional elements, such as sharp shapes, elicit higher LPC (Late Positive Complex) amplitudes, indicating stronger emotional reactions than positive elements. Positive design elements, like soft shapes and harmonious colors, significantly enhance consumer purchase intentions. However, negative emotions, such as those triggered by harsh materials or strong color contrasts, are more memorable and can reduce consumer interest in the brand over time. Designers are advised to prioritize shapes and materials that evoke positive emotions while being cautious with negative design elements, which may provoke stronger but adverse reactions. The study suggests strategies for optimizing emotional design, emphasizing emotional memory management and long-term brand perception to boost consumer loyalty and product desirability.